Effectiveness of different recruitment strategies in an RCT of a surgical device: experience from the Endobarrier trial. Issue 11 (14th November 2019) - Ruban, Aruchuna; Prechtl, Christina Gabriele; Glaysher, Michael Alan; Chhina, Navpreet; Al-Najim, Werd; Miras, Alexander Dimitri; Smith, Claire; P Goldstone, Anthony; Patel, Mayank; Moore, Michael; Ashrafian, Hutan; Byrne, James P; et al.
Abstract : Recruiting participants into clinical trials is notoriously difficult and poses the greatest challenge when planning any investigative study. Poor recruitment may not only have financial ramifications owing to increased time and resources being spent but could adversely influence the clinical impact of a study if it becomes underpowered. Herein, we present our own experience of recruiting into a nationally funded, multicentre, randomised controlled trial (RCT) of the Endobarrier versus standard medical therapy in obese patients with type 2diabetes. Despite these both being highly prevalent conditions, there were considerable barriers to the effectiveness of different recruitment strategies across each study site. Although recruitment from primary care proved extremely successful at one study site, this largely failed at another site prompting the implementation of multimodal recruitment strategies including a successful media campaign to ensure sufficient participants were enrolled and the study was adequately powered. From this experience, we propose where appropriate the early engagement and investment in media campaigns to enhance recruitment into clinical trials. Trial Registration: ISRCTN30845205 .